2000
DOI: 10.1016/s0092-8674(00)00091-x
|View full text |Cite
|
Sign up to set email alerts
|

CLIP170-like tip1p Spatially Organizes Microtubular Dynamics in Fission Yeast

Abstract: Rod-shaped fission yeast cells grow in a polarized manner, and unlike budding yeast, the correct positioning of the growth sites at cell ends requires interphase microtubules. Here we describe a microtubule guidance mechanism that orients microtubules in the intracellular space along the long axis of the cell, guiding them to their target region at the cell ends. This mechanism involves tip1p, a CLIP170-like protein that localizes to distal tips of cytoplasmic microtubules. In the absence of tip1p, microtubula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
274
2
12

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(303 citation statements)
references
References 54 publications
15
274
2
12
Order By: Relevance
“…These components could interact either directly with proteins of the mitochondrial outer membrane or through linker proteins. Previous studies have identified several proteins in S. pombe that interact with microtubules and concentrate at the cell tips [tip1p (21), tea1p (22), and tea2p (23)], but these species do not appear to play a direct role in facilitating microtubule interaction with mitochondria, because cells mutant for these components still distribute mitochondria toward the cell tips (B. Weir and M.P.Y., unpublished observations). Future genetic and biochemical approaches should lead to the identification of proteins that enable cells to couple microtubule and spindle dynamics with the productive and coordinated distribution of mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…These components could interact either directly with proteins of the mitochondrial outer membrane or through linker proteins. Previous studies have identified several proteins in S. pombe that interact with microtubules and concentrate at the cell tips [tip1p (21), tea1p (22), and tea2p (23)], but these species do not appear to play a direct role in facilitating microtubule interaction with mitochondria, because cells mutant for these components still distribute mitochondria toward the cell tips (B. Weir and M.P.Y., unpublished observations). Future genetic and biochemical approaches should lead to the identification of proteins that enable cells to couple microtubule and spindle dynamics with the productive and coordinated distribution of mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…Regulation of the local (25) or global (24) catastrophe rate (by appropriate microtubule-associated proteins) may tune the average length of the MTs to the appropriate value, and the mechanism will work independently of the size of the system. In small systems, where buckling forces are large, the mechanism, in addition, may be able to self-regulate.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…TOG and its orthologues all contain multiple HEAT repeats that may serve as a scaffold for other components to assemble into complexes (Neuwald and Hirano, 2000). In normal brain, TOG may function in cell morphogenesis and establishment of cellular polarity (Charrasse et al, 1995(Charrasse et al, , 1998Brunner and Nurse, 2000). It also has been suggested that proteins of the TOG family interact with the cell cortex to mediate motility (Schroer, 2001).…”
Section: Introductionmentioning
confidence: 99%